Analisis Penggunaan Afiks dalam Proses Pembentukan Kata di Iklan Megatron (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the use of affixation in the word formation process in Megatron advertisements, focusing on two main issues: how affixation is applied and what kinds of affixation errors are found. The research employs a descriptive qualitative method, with data collected through direct observation using the note-taking technique. The results show that affixation is used strategically and effectively to form words that not only comply with morphological rules but also serve persuasive and communicative functions in advertising. The use of prefixes, suffixes, and confixes in words such as berhadiah (with prizes), keuntungan (benefit), and kebutuhanmu (your needs) reflects a creative and adaptive linguistic approach tailored to the target audience, particularly younger generations. Moreover, the inclusion of popular elements and everyday language enhances the appeal of the message. Affixation in Megatron advertisements proves to be a crucial part of the communication strategy, aimed at building emotional closeness, strengthening brand image, and increasing marketing effectiveness.